Perlindungan Hukum Bagi Investor dalam Transaksi Saham pada Aplikasi Stockbit di Indonesia - Apriansyah, Nicko (Jurnal Jejak Hukum Indonesia (JHI), 2025)
This research is interesting to examine due to the numerous stock investment transactions on the Stockbit application in Indonesia. Therefore, the purpose of this article is to identify and analyze the implementation of legal protection for investors in stock transactions, as well as the impact of information disclosure on the Stockbit application in the capital market. The Stockbit stock application is one of the products in capital market investment that has been trusted and supervised by the Financial Services Authority (OJK) with permit number KEP 132/PM/1992. The OJK is also known to play an important role in providing understanding to the investing public regarding investment in the capital market, with the aim of enabling the investor community to understand all aspects of the advantages and disadvantages of investing in the capital market. Stock price fluctuations are seen as part of investment risk, so there are preventive and repressive efforts in the form of investor protection efforts such as applications and mandatory public companies that meet standards.